2007
DOI: 10.1016/j.virol.2006.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 2-mediated disease is reduced in mice lacking RNase L

Abstract: RNase L helps mediate the antiviral state induced by type I interferons (IFNalphabeta). Although herpes simplex virus (HSV) encodes inhibitors of the IFNalphabeta-induced antiviral response, the IFNalphabeta system serves the body as a first line of defense against HSV. We investigated whether RNase L limits HSV-2 replication and virulence. RNaseL(-/-) and wild-type C57BL/6 mice were infected intravaginally with HSV-2 strain 333. Although initial replication in the genital epithelium was similar, mice lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…However, the sustained lower HSV-2 replication in the CNS of Etg mice is likely related to lower TNF-␣ levels in the GT and CNS, thus suggesting that immunomodulatory effects might be less conducive to viral systemic dissemination and might be better for a disease outcome. Our results are in line with studies demonstrating that mice lacking RNase L or with neutralized TNF-␣ had a better disease outcome and reduced mortality with genital HSV-2 infection (16,81), hence confirming the beneficial role of Tr-mediated lower inflammation and viral translocation in genital HSV-2 infection. However, that only a trend of increased survival and a modest improvement in disease presentation were observed in Etg mice is a limiting factor in interpreting the significance of our observations and their extrapolations on human studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the sustained lower HSV-2 replication in the CNS of Etg mice is likely related to lower TNF-␣ levels in the GT and CNS, thus suggesting that immunomodulatory effects might be less conducive to viral systemic dissemination and might be better for a disease outcome. Our results are in line with studies demonstrating that mice lacking RNase L or with neutralized TNF-␣ had a better disease outcome and reduced mortality with genital HSV-2 infection (16,81), hence confirming the beneficial role of Tr-mediated lower inflammation and viral translocation in genital HSV-2 infection. However, that only a trend of increased survival and a modest improvement in disease presentation were observed in Etg mice is a limiting factor in interpreting the significance of our observations and their extrapolations on human studies.…”
Section: Discussionsupporting
confidence: 90%
“…However, a beneficial role of restricted antiviral and inflammatory responses was also recently highlighted (16,81). In vivo experiments using a murine transgenic model of lethal HSV-2 intravaginal infection showed that Etg mice, expressing human Tr, had reduced viral replication in the CNS, which could be attributed to a better containment and less efficient viral translocation/spread from the local target organ, GT, into the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 vhs deletion mutants show little or no increased sensitivity to type I IFN in vitro (38,59), and their replication in vivo is not significantly affected by IFN-␣/␤ (31). In contrast, we have shown that the major attenuating factor for vhs-deficient HSV-2 in vitro and in vivo is the type I IFN response (8,42), suggesting quantitative or qualitative differences in the capacity of HSV-1 and HSV-2 vhs proteins to modulate this branch of innate immunity. It seems logical that vhs may counter the IFN response by utilizing its ribonucleolytic activity to reduce IFN or IFN-stimulated gene expression, but the contribution of vhs ribonucleolytic activity to the overall effects of vhs on HSV-2 pathogenesis has not been examined.…”
mentioning
confidence: 62%
“…Surprisingly, lack of RNase L resulted in decreased pathology following vaginal infections of mice with HSV-2 strain 333 (29). There was less-severe genital and neurological disease as well as a delay in mortality in HSV-2 infected RNase L Ϫ/Ϫ mice than in identically infected WT mice.…”
Section: Poxviridaementioning
confidence: 95%